Adherence of people with type 1 diabetes to self-care activities / Adesão das pessoas com diabetes tipo 1 às atividades de autocuidado - Moura, Bernardo; Vidal, Diogo Guedes; Ferreira, Margarida (Journal of Nursing and Health, 2021)
Objective: to assess the adherence of people with type 1 diabetes to self-care activities. Method: quantitative study with 60 diabetics, from Porto, Portugal. The Self-Care Scale for Diabetes in its version translated and adapted to Portuguese was applied in January to February 2019. Results: respondents are mostly young (36.7%), employed (63.4%), female (73.3%), married (36.7%), high educated (60.0%) and diagnosed with recent diabetes (50.0%). Most have good mean adherence to self-care behaviors related to food (5.0), blood glucose monitoring (6.8), foot care (5.6) and medication (6.4). Regarding physical activity (2.6) and smoking, 73.3% of respondents say they smoked a cigarette in the last seven days lower adherence was identified. Conclusions: there is a need to develop educational programs to ensure a higher adherence to healthy lifestyles.